Comparison of Stroke Care Costs in Urban and Nonurban Hospitals and Its Association With Outcomes in New Zealand: A Nationwide Economic Evaluation. Issue 3 (28th February 2023) - Kim, Joosup; Cadilhac, Dominique A.; Thompson, Stephanie; Gommans, John; Davis, Alan; Barber, P. Alan; Fink, John; Harwood, Matire; Levack, William; McNaughton, Harry; Abernethy, Virginia; Girvan, Jacqueline; et al.
Abstract : Background: Although geographical differences in treatment and outcomes after stroke have been described, we lack evidence on differences in the costs of treatment between urban and nonurban regions. Additionally, it is unclear whether greater costs in one setting are justified given the outcomes achieved. We aimed to compare costs and quality-adjusted life years in people with stroke admitted to urban and nonurban hospitals in New Zealand. Methods: Observational study of patients with stroke admitted to the 28 New Zealand acute stroke hospitals (10 in urban areas) recruited between May and October 2018. Data were collected up to 12 months poststroke including treatments in hospital, inpatient rehabilitation, other health service utilization, aged residential care, productivity, and health-related quality of life. Costs in New Zealand dollars were estimated from a societal perspective and assigned to the initial hospital that patients presented to. Unit prices for 2018 were obtained from government and hospital sources. Multivariable regression analyses were conducted when assessing differences between groups. Results: Of 1510 patients (median age 78 years, 48% female), 607 presented to nonurban and 903 to urban hospitals. Mean hospital costs were greater in urban than nonurban hospitals (13 191 versus 11 635, P =0.002), as were total costs to 12 months (22 381 versus 17 217, P <0.001) and quality-adjusted life years to 12 months (0.54 versus 0.46, P <0.001). Differences in costs and quality-adjusted life years remained between groups after adjustment. Depending on the covariates included, costs per additional quality-adjusted life year in the urban hospitals compared to the nonurban hospitals ranged from 65 038 (unadjusted) to 136 125 (covariates: age, sex, prestroke disability, stroke type, severity, and ethnicity). Conclusions: Better outcomes following initial presentation to urban hospitals were associated with greater costs compared to nonurban hospitals. These findings may inform greater targeted expenditure in some nonurban hospitals to improve access to treatment and optimize outcomes.